Catalytic olefin polymerisation at short times: Studies using specially adapted reactors1. (30th April 2012) - McKenna, Timothy F. L.; Tioni, Estevan; Ranieri, Maria Maddalena; Alizadeh, Arash; Boisson, Christophe; Monteil, Vincent
Abstract Despite the fact that the very early stages (several tens of seconds) of catalysed olefin polymerisation processes appear negligibly short with respect to the residence time of most industrial reactors, they are critical in terms of catalyst activation, obtaining good particle morphology, and avoiding irreparable problems caused by particle overheating. The different types of reactors that have been used over the course of the past few years are discussed in this feature article. It is shown that despite the difficulties encountered in finding the perfect experimental tool for this purpose, different configurations of stopped flow reactors can be used successfully to explore different aspects of what happens to the catalyst (supported and molecular) during these critical moments of polymerisation. © 2012 Canadian Society for Chemical Engineering